Comparative and synergistic impacts of lime and biochar on soil properties, nitrogen transformation, and microbial function in acidic soils under tobacco cropping - Zhang, Bianhong; Tang, Lina; Chen, Zhicheng; Chen, Xiaoyan; You, Lindong; Pan, Ruixin; Chen, Ting; Liu, Yifei; Lin, Wenxiong; Huang, Jinwen (Frontiers in Plant Science, 2025)
IntroductionLime and biochar are widely utilized to enhance nitrogen utilization in crops grown on acidic soils, though each has its own set of limitations. Understanding their combined effects is crucial for optimizing soil remediation strategies.MethodsThis study investigates the impact of lime and biochar on nitrogen utilization efficiency (NUE) in a tobacco monoculture system, which has been practiced for 20 years on acidified soils in Fuzhou, southeastern China, over the period from 2021 to 2022. Four treatments were applied: control (CK), lime alone (L), biochar alone (B), and a lime-biochar combination (L+B).ResultsThe results indicated that all treatments significantly improved NUE, with increases ranging from 20.07% to 27.17% compared to CK. Biochar (B) was more effective than lime (L), and the combined treatment (L+B) showed comparable effects to biochar alone. Correlation analysis revealed that increases in soil pH and exchangeable base cations facilitated nitrogen transformation, thereby enhancing NUE. Lime treatments (L, L+B) promoted nitrification potential in rhizosphere soil, whereas biochar application (B, L+B) resulted in elevated nitrate nitrogen content. Microbial functional analysis indicated that lime (L, L+B) enhanced nitrification, while biochar (B, L+B) fostered dissimilatory nitrate reduction, thereby improving nitrogen retention. Pearson correlation analysis demonstrated a strong positive relationship between dissimilatory nitrate reduction and both soil alkali-hydrolyzable nitrogen and nitrate nitrogen contents.ConclusionThese findings suggest that lime enhances nitrification, while biochar promotes nitrate retention, together increasing soil nitrogen availability. The combined application of lime and biochar integrates these benefits, yielding results comparable to biochar alone. This study offers valuable insights into the synergistic use of lime and biochar for mitigating soil acidification and optimizing nitrogen management in agricultural systems.